Development of an instrument to evaluate high school students' chemical symbol representation abilities. Issue 4 (8th September 2017) - Wang, Zuhao; Chi, Shaohui; Luo, Ma; Yang, Yuqin; Huang, Min
Abstract : Chemical symbol representation is a medium for transformations between the actual phenomena of the macroscopic world and those of the sub-microscopic world. The aim of this study is to develop an instrument to evaluate high school students' chemical symbol representation abilities (CSRA). Based on the current literature, we defined CSRA and constructed a four-level measurement framework validated by expert review. After that, an initial measurement instrument was developed based on the framework. Then, 52 students of Grade 10 and 56 students of Grade 11 were selected from school A to participate in the first round of testing. During the data analysis, Rasch measurement was used to investigate and improve the quality of the instrument. After that, 55 Grade 10 students and 57 Grade 11 students from school B participated in the second-round of testing, and the Rasch analysis results demonstrated good reliability and validity of measures based on the CSRA framework.